The Bioequivalence of Two Peficitinib Formulations, and the Effect of Food on the Pharmacokinetics of Peficitinib: Two‐Way Crossover Studies of a Single Dose of 150 mg Peficitinib in Healthy Volunteers. Issue 3 (3rd July 2020) - Shibata, Mai; Toyoshima, Junko; Kaneko, Yuichiro; Oda, Kazuo; Kiyota, Tsuyoshi; Kambayashi, Atsushi; Nishimura, Tetsuya
Abstract: The marketed tablet formulation of peficitinib differs from the tablet used during the clinical trials. The bioequivalence of the marketed formulation and developmental tablet, and the food effect on the marketed formulation, were analyzed in 2 Japanese open‐label, randomized, 2‐way crossover studies in healthy male volunteers. Volunteers received a single oral dose of the marketed 150‐mg peficitinib tablet under fasted conditions (bioequivalence), and under fed or fasted conditions (food effect). Bioequivalence was compared with the developmental 150‐mg tablet. Samples for pharmacokinetic analysis were collected before dose and ≤72 hours after dose. Safety assessments included adverse events, vital signs, and laboratory variables. In total, 40 and 18 subjects were randomized to the bioequivalence and food effect studies, respectively. The 2 peficitinib formulations were bioequivalent (90% confidence intervals of the geometric mean ratios for Cmax and AUCt of peficitinib were within predefined limits of 0.8 to 1.25). The AUClast and the Cmax of the marketed tablet were 36.8% and 56.4% higher, respectively, under fed versus fasted conditions. Peficitinib was well tolerated. The marketed 150‐mg tablet formulation of peficitinib was bioequivalent to the developmental 150‐mg formulation, with no discernible safety differences. Bioavailability increased under fed conditions with the marketed tablet formulation.